3D Bioprinted Liver-on-a-Chip for Drug Cytotoxicity Screening - Huh, JunTae (2024)
Tissues on a chip are sophisticated three-dimensional (3D) in vitro microphysiological systems designed to replicate human tissue conditions within dynamic physicochemical environments. However, the current fabrication methods for tissue spheroids on a chip require multiple parts and manual processing steps, including the deposition of spheroids onto prefabricated ‘‘chips.’’ These challenges also lead to limitations regarding scalability and reproducibility. To overcome these challenges, we employed 3D printing techniques to automate the fabrication process of tissue spheroids on a chip. This allowed the simultaneous high-throughput printing of human liver spheroids and their surrounding polymeric flow chamber ‘‘chips’’ containing inner channels in a single step. The fabricated liver tissue spheroids on a liver-on-a-chip (LOC) were subsequently subjected to dynamic culturing by a peristaltic pump, enabling assessment of cell viability and metabolic activities. The 3D printed liver spheroids within the printed chips demonstrated high cell viability (>80%), increased spheroid size, and consistent adenosine triphosphate (ATP) activity and albumin production for up to 14 days. Furthermore, we conducted a study on the effects of acetaminophen (APAP), a nonsteroidal anti-inflammatory drug, on the LOC. Comparative analysis revealed a substantial decline in cell viability (<40%), diminished ATP activity, and reduced spheroid size after 7 days of culture within the APAP-treated LOC group, compared to the nontreated groups. These results underscore the potential of 3D bioprinted tissue chips as an advanced in vitro model that holds promise for accurately studying in vivo biological processes, including the assessment of tissue response to administered drugs, in a high-throughput manner.